Discussion group networks in occupational medicine: A tool for continuing education to promote the integration of workers with disabilities. Issue 4 (5th February 2018) - Rinsky‐Halivni, Lilah; Lerman, Yehuda
Abstract : Background: Despite their legal rights, individuals with disabilities face numerous obstacles to integration in the workplace which can result in their discharge from the labor force. Currently occupational physicians have few resources to help decide whether to integrate disabled workers in pre‐placement, or in cases of return‐to‐work. Methods: A network of 13 discussion groups comprised of the occupational physicians of each regional clinic of a large Health Maintenance Organization (HMO) in Israel was created to deal with disability management dilemmas. A moderator compiles and shares the physicians' opinions and experiences with all network members thus assisting the consulting physician in decision‐making. Results: Successful management of three representative cases is described to illustrate real‐life implementations of this network. Conclusion: The network enables both the consulting and other physicians to tap a large knowledge base and decision‐making experience concerning cases of occupational disability management, contributing to professional development and improved service delivery.